2013
DOI: 10.1089/aid.2013.0097
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Evidence That Microbial Translocation Occurs in HIV-Infected Children in the United Kingdom

Abstract: Microbial translocation (MT) from the gut is implicated in driving immune activation, increasing morbidity and mortality in HIV. We used bacterial 16S rDNA PCR, Sanger sequencing, and high-throughput sequencing to identify microbial DNA in the bloodstream of HIV-infected children in London, United Kingdom. Blood samples were collected from sequential children attending the HIV clinic at Great Ormond Street Hospital, London. DNA extraction, broad range 16S rDNA PCR, and standard Sanger sequencing were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
2
8
0
1
Order By: Relevance
“…This has been observed in HIV-infected adults [10]. Our results support previous observations that HIV-infected children have gut-associated lymphoid tissue injury resulting in persistent microbial translocation and/or defects in LPS clearance mechanisms [11][12][13]15,16].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This has been observed in HIV-infected adults [10]. Our results support previous observations that HIV-infected children have gut-associated lymphoid tissue injury resulting in persistent microbial translocation and/or defects in LPS clearance mechanisms [11][12][13]15,16].…”
supporting
confidence: 91%
“…During the acute phase of infection, the main driver of immune activation appears to be high levels of virus with other factors such as microbial translocation more important in chronic infection [8]. Few studies have focused on immune activation and microbial translocation profiles of HIVinfected children [11][12][13].…”
mentioning
confidence: 99%
“…Collection and DNA extraction was carried out as previously described [2]. Extracted DNA was amplified twice in separate PCR reactions, pyrosequenced on a 454 FLX Titanium (Roche) and the subsequent sequences analysed as previously described [4]. Reads were filtered above a level to remove spurious Operational Taxonomic Units generated by PCR or sequencing error (had to be present above 1% relative abundance in at least one sample).…”
Section: Methodsmentioning
confidence: 99%
“…Brenchley et al [11] first reported increased circulating LPS in both HIV-infected humans and SIVinfected rhesus macaques during chronic infection. More recently, clinical investigations [42,43] have confirmed that microbial translocation is also a major source of immune activation and may contribute to the rapid disease progression in HIV infected children [44]. But, in another study, Wittkop et al illuminated that autoimmune response and microbial translocation were not associated with immune activation [45].…”
Section: Microbial Translocation and Immune Active In Hiv/siv Infectionmentioning
confidence: 99%